The effect of El Niño Southern Oscillation cycles on the decadal scale suspended sediment behavior of a coastal dry‐summer subtropical catchment. Issue 2 (11th August 2014) - Gray, Andrew B.; Pasternack, Gregory B.; Watson, Elizabeth B.; Warrick, Jonathan A.; Goñi, Miguel A.
Abstract Rivers display temporal dependence in suspended sediment–water discharge relationships. Although most work has focused on multi‐decadal trends, river sediment behavior often displays sub‐decadal scale fluctuations that have received little attention. The objectives of this study were to identify inter‐annual to decadal scale fluctuations in the suspended sediment–discharge relationship of a dry‐summer subtropical river, infer the mechanisms behind these fluctuations, and examine the role of El Niño Southern Oscillation climate cycles. The Salinas River (California) is a moderate sized (11 000 km2), coastal dry‐summer subtropical catchment with a mean discharge (Qmean) of 11.6 m3 s−1. This watershed is located at the northern most extent of the Pacific coastal North America region that experiences increased storm frequency during El Niño years. Event to inter‐annual scale suspended sediment behavior in this system was known to be influenced by antecedent hydrologic conditions, whereby previous hydrologic activity regulates the suspended sediment concentration–water discharge relationship. Fine and sand suspended sediment in the lower Salinas River exhibited persistent, decadal scale periods of positive and negative discharge corrected concentrations. The decadal scale variability in suspended sediment behavior was influenced by inter‐annual to decadal scale fluctuations in hydrologic characteristics, including: elapsed time since small (~0.1 × Qmean), and moderate (~10 × Qmean) threshold discharge values, the number of preceding days that low/no flow occurred, and annual water yield. El Niño climatic activity was found to have little effect on decadal‐scale fluctuations in the fine suspended sediment–discharge relationship due to low or no effect on the frequency of moderate to low discharge magnitudes, annual precipitation, and water yield. However, sand concentrations generally increased in El Niño years due to the increased frequency of moderate to high magnitude discharge events, which generally increase sand supply. Copyright © 2014 John Wiley & Sons, Ltd.